A Review On Diagnosis And Treatment Of Gridhrasi With Ayurvedic Approac - Karande, Shraddha D; S S; Hudedmani, Irappa; Badiger, M S (International Research Journal of Ayurveda & Yoga, 2021)
Introduction-Gridhrasi is painful and troublesome disease. If not treated on time it can led to serious conditions. Signs and symptoms of Gridhrasi are very similar to Sciatica. Causes of Gridhrasi are poor lifestyle, stress, improper posture, continuous jerky movements, Long traveling, that put maximum pressure on the spine and pelvis. About 60%-80% of people get affected by low back pain and 5% of those become victims of sciatica. Material and methods-The Review of literature includes screening of classical literature, Contemporary Ayurvedic Literature and Internet Sources related to Gridhrasi were explored to collect sufficient data for thestudy.Aimsandobjectives-TassessandelaboratetheetiologicalcomponentsofGridhrasi.ResultandConclusion-Ayurveda offers ample of better options in management of Gridhrasi. To fulfil the expectations from the Ayurvedic field, and to find out more effective and safe therapy for Gridhrasi.